Studies of planting and floral induction seasons in pineapple plants, cv. Perola - Choairy, Salim Abreu; de Oliveira, Eliazar Felipe; Fernandes, Pedro Dantas (Pesquisa Agropecuaria Brasileira, 1994)
The present work was carried out with the objective to study four planting seasons, and floral induction in three different ages, on the quantitative and qualitative characteristics of pineapple Ananas comosus, (L.) Merril, cv. Perola. The experiment was conducted in Sapé, PB, Brazil, in Red-Yellow Podzol. Slips (200g) were used as planting material. The results showed that the most favorable planting season was May, with the floral induction in the 12th. month. The least favorable planting season was August. The floral induction, when the plants were 8 months old, resulted in lower fruit production, in all planting seasons, and more acid fruits. The fruits formed under rainy season had lower brix content, while acidity was greater.
Keywords: Ananas comosus; production seasons